Політика возз’єднання сімей як складник імміграційної політики Іспанії - Коцан, В. Ю.; Kotsan, V. Yu. (Східноєвропейський національний університет ім. Лесі Українки, 2015)
Розглянуто завдання та ключові моменти імміграційної політики. Висвітлено політику возз’єднання сімей як інструмент регулювання імміграції в Іспанії. Увага звернута на особливості процедури возз’єднання сімей. The objectives and key points of immigration policy are considered. Family reunification policy is outlined as a tool for regulating immigration in Spain. An attention is paid to the peculiarities of family reunification procedures. Key words: immigration policy, the policy of family reunification, immigration, Spain.
Family Reunification Policy as a Part of Spain's Immigration Policy
Keywords: імміграційна політика; політика возз’єднання сімей; імміграція; Іспанія; immigration policy; the policy of family reunification; immigration; Spain